Fashion archives, museums and collections in the age of the digital. Issue 1 (1st June 2019) - Pecorari, Marco
Currently there is a trend for the digital in archives, collections and museums of fashion. Not only are museums digitalizing and giving free online access to their collections, but new types of digital fashion archives and collections are emerging thanks to the advent of the Internet and the proliferation of social media. This article explores this shift, functioning as both an introduction to this thematic issue and as a mapping of the different transformations lived by archives, museums and collections in the age of the digital. How has the digital effected a different understanding of fashion in museums, archives and collections? What types of challenges is the digital bringing to museum practitioners and scholars? In the following sections, my aim is to emphasize some areas of transformation, highlighting four contested fields: (1) the dichotomies between archives/museums and the digital in relation to issues of access and fashion heritage; (2) the shift from material to digital archives and the effects of practices of digitalization of fashion archives; (3) the emergence of new ephemeralities and the utopic practices of conserving online fashion; and (4) the expansion of the understanding of fashion archives and the consequent effects on users' agency and research practices. Drawing on digital studies, archive theory, museum studies, heritage studies and fashion studies, I reflect on these shifts, contextualizing the articles published in this thematic issue and revisiting the scope of some of the projects I developed in collaboration with the EU-funded project Europeana Fashion.